Interpreting Skills to The Student's Mathematical Problem-Solving Process - Badi'ah, Siti; As'ari, Abdur Rahman; Hidayah, Indriati Nurul (Universitas Suryakancana, 2024)
The objective of the study was to analyze the teacher's skills, and the interpreting skills of the teacher in identifying the student's ability to solve problems based on the stages developed by Swartz (1998), i.e. generating ideas, clarifying ideas, and assessing the reasonableness of ideas. This type of research is qualitative descriptive research. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. The students involved in solving mathematical problems are named A, B, C, and D. The four teachers involved as research subjects are represented by G1, G2, G3, and G4. Each teacher is given four student answers which are then analyzed. Interpreting skills of each subject are developed by researchers in the way of interviews. The interviews conducted are semi-structured, then the results of the interviews are analyzed by the researchers. Data analysis techniques using the Miles and Huberman model are: 1) data reduction; 2) data display; and 3) concluding drawing. The results show that G2 and G4 have complete interpretation skills, whereas G1 and G3 have interpreting skills that only generate and clarify ideas.